O enunciatário da revista VEJA: contribuição para discussões sobre indústria cultural e cultura de massa - Palomino, Rafael Henrique [UNESP]; Marchezan, Renata Maria Facuri Coelho [UNESP] (My University, 2012)
This work intends to “test” two theories about mass cultural products – one that understands them as syncretic and plural and another that sees them as homogenizators and aimed to a mixed audience. We chose Veja magazine as the object of this study and tried to understand how its internal sessions bring in their readers, with the goal of verifying whether readers shared characteristics. In the affirmative case, Veja would be directed to a specific reader; otherwise, it would be a syncretic cultural product. This answer should give us basis to reflect upon the opposition between both ways of thinking about mass culture and help us take a stand on this discussion. Obviously, we do not intend to give a definitive answer to the opposition between these two tendencies. The limits of this work are given by the investigated object itself: we intend to verify empirically how Veja, as a cultural product, solves the contradiction that the co-existence of these two opposite theories point about mass society.

Este trabalho tem a intenção de, por assim dizer, “testar” duas teorias sobre os produtos culturais de massa — uma que os concebe como sincréticos e plurais e outra que os vê como homogeneizadores e voltados a um público médio. Tomamos como objeto a revista Veja e buscamos conferir como as seções internas da revista instauravam seus enunciatários, com a intenção de verificar se eles tinham semelhanças. Em caso afirmativo, Veja seria um produto cultural dirigido a um leitor específico; caso contrário, ela seria um produto cultural sincrético. Tal resposta nos daria lastro para refletir sobre a oposição entre as duas vertentes da análise da cultura de massa e tomar posição frente a elas. Claro que não pretendemos responder em definitivo à oposição entre as duas tendências. Os limites deste trabalho são dados pelo próprio objeto investigado: pretendemos verificar empiricamente como Veja, enquanto produto cultural, resolve a contradição que a coexistência dessas teorias opostas aponta sobre a sociedade de massa.
Keywords: ethos; pathos; enunciatário